Study of Socio-Economic-Cultural Impacts and Community Health Due to Oil and Natural Gas Exploration Activities in the Tuban Oil and Gas Field - Ai Siti Patimah; Sigit Heru Murti; Agus Prasetya (Faculty of Geography, Universitas Gadjah Mada, 2023)
This research is a social study by capturing several problems in the oil and gas sector combined with literature studies that have relevant themes. This study aims to determine the social, economic, cultural and health impacts of the oil and gas company's exploration activities in the Tuban Oil and Gas Field. Data collection was in the form of primary data and secondary data in semester II of 2018. The methods used in this study were qualitative and quantitative methods. Qualitative methods taken from primary data, namely observation and interviews. Primary data were obtained through direct observation and interviews with respondents selected by purposive sampling. The quantitative method uses secondary data obtained from research documents and reports relating to government agencies and companies. Primary data and secondary data were combined and then conducted interviews to obtain deeper information using the forum group discussion (FGD) method. The final data obtained were analyzed using descriptive statistical methods. The results of the study show that there are jobs for local workers, but the information is still not transparent and most of the jobs are temporary projects. Most people know and feel the benefits of the presence of oil and gas companies in their area. The community expects the company's attention to reduce people's concerns about oil and gas activities. Conflicts often occur due to delays in the disbursement of compensation funds and the implementation of CSR, as well as several oil and gas company activities that have a direct impact on the community. The company's efforts to boost the local economy by increasing employment opportunities and increasing wage rates. Meanwhile, in terms of public health, it cannot be determined with certainty whether there is a correlation between disease and the activities of oil and gas companies. In general, oil and gas companies have a positive impact on the community around the working areas of oil and gas companies.